2014
DOI: 10.1063/1.4893953
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Kondo resonance in the d-CoPc/Au(111) adsorption system

Abstract: By combining the density functional theory (DFT) and a hierarchical equations of motion (HEOM) approach, we investigate the Kondo phenomena in a composite system consisting of a dehydrogenated cobalt phthalocyanine molecule (d-CoPc) adsorbed on an Au(111) surface. DFT calculations are performed to determine the ground-state geometric and electronic structures of the adsorption system. It is found that the singly occupied dz(2) orbital of Co forms a localized spin, which could be screened by the substrate condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 69 publications
1
46
0
1
Order By: Relevance
“…6.2). The Kondo effect [662] observed for this structure (while no Kondo effect was observed for intact CoPc) indicated reduced Co-Au coupling [350,530,669]. Similar decoupling experiments were performed with partially dehydrogenated CoPc at monoatomic steps on Au(1 1 1) [530,670].…”
Section: Adsorption On Coinage Metal Substratessupporting
confidence: 53%
“…6.2). The Kondo effect [662] observed for this structure (while no Kondo effect was observed for intact CoPc) indicated reduced Co-Au coupling [350,530,669]. Similar decoupling experiments were performed with partially dehydrogenated CoPc at monoatomic steps on Au(1 1 1) [530,670].…”
Section: Adsorption On Coinage Metal Substratessupporting
confidence: 53%
“…The HEOM‐QUICK program has been utilized in conjunction with DFT programs such as the Vienna ab initio simulation package (VASP) to realize first‐principles‐based simulation on magnetic molecular impurities. With the present HEOM‐QUICK code, a DFT + HEOM simulation proceeds as follows . First the geometric and electronic structures of the magnetic impurity system are calculated with DFT methods.…”
Section: Heom‐quick: Numerical Algorithms and Techniquesmentioning
confidence: 99%
“…In the pioneering STM experiment performed by Zhao et al, it has been found that CoPc molecules absorbed on Au (111) surface does not exhibit Kondo phenomenon; while Kondo signature is clearly observed with the eight edge hydrogen atoms on the four benzene rings cut away from the CoPc molecule. The Kondo effect of a dehydrogenated CoPc (d‐CoPc) molecule absorbed on Au (111) surface has been investigated by combing DFT and HEOM approaches …”
Section: Applications Of the Heom‐quick Programmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been employed to investigate a wide range of equilibrium and nonequilibrium and static and dynamic properties of strongly correlated quantum impurity systems [49,52,53,57,58]. The numerical results of the HEOM approach are considered to be quantitatively accurate, as long as the results converge with respect to the truncation of the hierarchy.…”
Section: B the Heom Approach For Strongly Correlated Quantum Impuritmentioning
confidence: 99%